2018
DOI: 10.1136/bmjopen-2018-024528
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour change interventions for the management of Raynaud’s phenomenon: a systematic literature review

Abstract: ObjectivesRaynaud’s phenomenon (RP) is a significant cause of morbidity. Vasodilator medications cause unwanted adverse effects, with behavioural and lifestyle changes forming the mainstay of self-management; this is difficult to implement successfully. The objectives of this study were to evaluate the efficacy of behaviour change interventions for RP and identify learning points for future treatment development.DesignSystematic literature review and narrative synthesis of findings.Data sourcesEMBASE, MEDLINE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
6
0
2
Order By: Relevance
“…The patients were given behavioral interventions before discharge and were instructed to pay attention to keeping their digits warm and avoiding cold exposure. Although there was little evidence demonstrating that daily lifestyle habits influenced RS pathogenesis [ 10 , 11 ], patients should be encouraged to quit smoking to promote vasoconstriction [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The patients were given behavioral interventions before discharge and were instructed to pay attention to keeping their digits warm and avoiding cold exposure. Although there was little evidence demonstrating that daily lifestyle habits influenced RS pathogenesis [ 10 , 11 ], patients should be encouraged to quit smoking to promote vasoconstriction [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is of interest because experts from the Scleroderma Clinical Trials Consortium and the Canadian Scleroderma Research Group, in general, propose an additive approach (with drugs used in combination) for the treatment of SSc-RP (9). Onethird (29.7%) of patients also indicated that they are keen to consider nonpharmacologic approaches to management, although the evidence base to support these interventions at present are limited (18).…”
Section: Discussionmentioning
confidence: 99%
“…A vizsgálatok többsége az 1980-90-es években készült, és a leggyakrabban 'biofeedback' készülékeket alkalmaztak, amelyeket esetenként kombináltak autogén tréninggel. A vizsgálatok vegyes eredménnyel zárultak, és nem tekinthetők konkluzívnak [57,58]. Annak ellenére, hogy a Raynaudszindróma kezelésében az elsődleges az életvezetési tanácsadás, az utóbbi 10-20 évben nem történt olyan kutatás, amely pszichológiai szintű segítségnyújtás bármilyen módszerének hatékonyságát vizsgálta volna.…”
Section: éLetvezetési Tanácsadásunclassified
“…Annak ellenére, hogy a Raynaudszindróma kezelésében az elsődleges az életvezetési tanácsadás, az utóbbi 10-20 évben nem történt olyan kutatás, amely pszichológiai szintű segítségnyújtás bármilyen módszerének hatékonyságát vizsgálta volna. Egy új áttekintő tanulmányban [58] számos fontos javaslatot tesznek a további vizsgálatok számára. Kiemelik: fontos, hogy a vizsgálat megfelelő konceptuális kerettel rendelkezzen, a legfrissebb diagnosztikus kritériumokat alkalmazzák, az elsődleges és a másodlagos kórforma külön legyen kezelve, objektív és szubjektív (például önkitöltős kérdőív) mérés egyaránt történjen, a vizsgálatvezető elvárásai ne befolyásolhassák az eredményt, és megfelelő elemszámú randomizált, kontrollált mintákkal történjen a vizsgálat.…”
Section: éLetvezetési Tanácsadásunclassified